Transgender an At-Risk Population During and Following Emergencies and Disasters - Fontanez, Joshua Aaron (2019)
The experiences and needs of transgendered individuals immediately following a natural or human-caused disaster are largely ignored in practice and absent from previous academic literature. Using Schneider and Ingram's conceptualization of the social construction of target populations as a theoretical framework, the purpose of this study was to investigate the experiences and perspectives of transgendered people who sought shelter in the aftermath of a natural disaster in 2018. Data were collected through interviews with 12 displaced, transgendered individuals to explore their experiences while staying at shelters in 2018. Interview data were transcribed, inductively coded, and then a thematic analysis procedure was applied. According to the key findings, participants perceived internal threats at shelters, which may have prohibited or restricted others in the same population from seeking shelter assistance. Additionally, participants perceived that a lack of understanding of the transgender community may have resulted in dissatisfactory services being provided. Most participants in this study perceived that the biases associated with negative stereotypes were persistent and pervasive, which may have resulted in disparate treatment from cisgender community members. The positive social change implications stemming from this study include recommendations to government officials and shelter staff regarding techniques to ensure that shelter services are provided in fair and equitable ways, including the need for additional training related to the unique needs of transgendered populations. Implementing these recommendations may improve shelter conditions for the transgender community and reduce the risks associated with going to evacuation shelters to secure housing during times of disaster